Correlation of Lacunar Infarct on Head Ct Scan with Dysarthria in Haji Adam Malik General Hospital in 2019 - Asysyarif, Abdurrahman; Daulay, Elvita Rahmi; Ritarwan, Kiking (CoinReads Media Prima, 2023)
Introduction: Stroke is the main cause of mortality and morbidity in Indonesia. Dysarthria is a symptom that can be seen from stroke. These symptoms occur in 15% of stroke events. Dysarthria is a motor speech disorder. Atypical lacunar stroke (ALS) is a stroke subtype that rarely occurs in one in 14 lacunar strokes or occurs in 6.8% of lacunar strokes, where isolated dysarthria or dysarthria facial paresis is the most common form of presentation. Method: This study is an observational analytic study with a case-control type of research with the aim of knowing the relationship between CT scan images of lacunar infarcts and dysarthria in ischemic stroke patients. The population in this study were all medical records of stroke patients who went to the Department of Neurology at the Haji Adam Malik General Hospital (RSUPHAM) Medan for a period of one year from January 1, 2019 to December 31, 2019 who underwent a head CT scan for 18 patients. Results: The subjects on the CT scan results of lacunar infarction with dysarthria 18 people (72%), and 7 people (28%) on the CT scan results there is no lacunar infarction. The same number and percentage were also found in the non-chivalrous control group. The test results obtained p value = 1,000 and odd ratio = 1.00, in other words there is no significant relationship between lacunar infarct and dysarthria. Conclusion: No significant relationship was found between the incidence of lacunar infarction and the incidence of dysarthria. The population with the most lacunar infarcts is men, hypertension, obesity, hypercholesterolemia, smoking and diabetes.